Development of Augmented Reality Learning Media for Plantae Material in Class X Biology Subjects Using Arttoolkit - Yoga Putra Jaya; Agus Efendi; Endar Suprih Wihidayat (Journal of Informatics and Vocational Education, 2023)
A lot of material discusses Plantae, so interesting learning is needed so that students can easily accept and understand the material provided. AR technology can facilitate learning Plantae in the classroom. This research develops AR-based "Plantar" media. The application was developed based on Android to make it easier for students to learn plantae material in biology subjects. Plantar was developed using the Ionic platform and ARToolkit as the AR feature development library. Plantar uses a PWA (Progressive Web App) type to open its use via a browser. Field tests were conducted on 36 Kebakkramat SMA students to assess presence, affordance, and usability. The results showed that the Plantar media received a very good rating and did not require repair. So that the general public can use the Plantar application, especially high school students, to study Plantae material in an exciting way using the AR feature. In the future, it is hoped that the Plantar application will be useful in helping the learning process of Plantae material. Keywords: Learning Media, Augmented Reality, ARToolkit